Preparation, Identification and Antioxidant Properties of Black-Bone Silky Fowl (Gallus gallus domesticus Brisson) Iron(II)-Oligopeptide Chelate - Huanglei Pan; Shasha Song; Qiuyue Ma; Hui Wei; Difeng Ren; Jun Lu (Food Technology and Biotechnology, 2016)
Black-bone silky fowl iron(II)-oligopeptide chelate was synthesized from iron(II) solution and the black-bone silky fowl oligopeptide, which was extracted from the muscle protein of black-bone silky fowl (Gallus gallus domesticus Brisson). Orthogonal array analysis was used to determine the optimal conditions for the iron(II)-oligopeptide chelate preparation. Ultraviolet-visible (UV-Vis) spectroscopy, electron microscopy, and Fourier transform infrared (FTIR) spectroscopy were used to identify the structure of iron(II)-oligopeptide chelate. 2-Diphenyl-1-picrylhydrazyl (DPPH) and superoxide radical scavenging assays were performed to compare the antioxidant abilities of the black-bone silky fowl oligopeptide and iron(II)-oligopeptide chelate. The optimal conditions for iron(II) oligopeptide chelate preparation were 4 % of the black-bone silky fowl oligopeptide and a ratio of the black-bone silky fowl oligopeptide to FeCl2·4H2O of 5:1 at pH=4. Under these conditions, the chelation rate was (84.9±0.2) % (p<0.05), and the chelation yield was (40.3±0.1) % (p<0.05). The structures detected with UV-Vis spectroscopy, electron microscopy and FTIR spectra changed significantly after chelation, suggesting that Fe(II) ions formed coordinate bonds with carboxylate (-RCOO¯) and amino (-NH2) groups in the oligopeptides, confirming that this is a new oligopeptide-iron chelate. The iron(II)-oligopeptide chelate had stronger scavenging activity towards DPPH and superoxide radicals than did the black-bone silky fowl oligopeptide.